Role of Digital Technologies for Sustainable Innovation and Value Creation: A Narrative Review - VK, Rajan Kumar (Rupandehi Campus Journal, 2022)
The purpose of this review paper is to examine the role of cutting-edge technologies in various aspects of supply chain processes as a part of a strategic plan for driving sustainable innovation. Furthermore, the study also explores the impact of digitization on modernizing supply chain operations from an industry 4.0 perspective for value creation. The study implies a narrative qualitative review for the interpretation of analyzed data from the selected articles and is based on analytical, and logical reasoning to determine patterns, relationships, or trends within the realm of the chosen subject matter for this study. The literature reveals that the implication of cutting-edge technologies as a strategic part of supply chain operations is significantly important for sustainable innovation and value creation of the company. The findings of the study will have implications for the supply chain managers for creating value for their organizations, stakeholders, and customers. Moreover, the study will also provide the essential knowledge for the development of the theory in the same domain for future researchers.